Let's talk about sext : gendered millennial perceptions of sexting in a cyborg society - Meyer, Melissa Isabella (Institute of Criminology, 2016)
In a cyborg society where people exist both organically and via technology, sexual expression and interaction via technology has become 'normal'. The controversy surrounding sexting stems from contemporary literature and media portraying it as coercive, harmful and unacceptable, with particular reference to young females. Qualitative data on this phenomenon is extremely limited and biased, potentially resulting in unjust limitations and restrictions. This study investigates Millennial sexting behaviour by considering general and gendered perceptions of sexting to better understand the phenomenon; its risks, benefits, and the practice itself. An exploratory mixed methods study amongst university students (N = 579) revealed expected and unexpected findings. Respondents acknowledged sexting's risks, while the benefits of and motivations for sexting were emphasised with little evidence of negative pressure. It is argued that the benefits of sexting greatly outweigh the potential risks, but moreover, that sexting is a primarily feminist practice that holds much promise. The need for sextual education and awareness of sext-consent is examined, as theoretical and policy implications are discussed.